The enchanted sled - Wahl, Jan.; Félix, Monique (Mankato, MN : Creative Editions, 2005)
Illustrations and rhyming text extol the joys of a wondrous sled ride.
F
b
b
Keywords: Sledding -- Fiction; Stories in rhyme